Breast cancer awareness and breast screening practice among women in Yogyakarta - Susi Ari Kristina; Nada Nisrina Salsabila (Journal of Global Pharma Technology, 2020)
Background: Low public knowledge and understanding, contributing to late diagnosis, has identified cancer morbidity and mortality from breast cancer. This study was designed to describe breast cancer knowledge and awareness and evaluate breast screening practice among Yogyakarta women. Methods: A cross-sectional study of 350 low socioeconomic women in rural and urban Yogyakarta areas was conducted using a validated self-designed structured questionnaire. Analyzing data using descriptive statistics. Results: A vast majority of respondents knew that breast cancer is a severe disease (85.14%) and can be detected as early as possible (60.00%). Genetic and family cancer history was the best accepted risk factor for breast cancer (61.43%), followed by oral contraception (44.57%), radiation (31.43%), smoking (28.86%) and alcohol intake (21.71%). Over half of respondents (65.14%) correctly identified niple and color discharge as one of the symptoms of breast cancer, followed by breast lump (60.00%), breast swelling (56.29%) and breast fluid (44.57%). While 56.57 percent of respondents had heard of breast self-examination ( BSE) and mammography, only 26.86 percent of respondents had regularly performed BSE, and only 28.00 percent of respondents reported daily mammography. A large proportion of respondents (72.86%) never diagnosed breast cancer. Conclusion: In Yogyakarta, the study reported inadequate breast cancer awareness and poor breast screening practice among women with low socioeconomic status aged 20-50 years. Health care professionals are fairly required to educate women about breast cancer and promote early detection and breast cancer screening programs to prevent and reduce breast cancer incidence and mortality.